2002
DOI: 10.1159/000062997
|View full text |Cite
|
Sign up to set email alerts
|

Alterations of Quantitative EEG and Mini-Mental State Examination in Interferon-α-Treated Hepatitis C

Abstract: We have recently observed a diffuse slowing of brain waves using serial quantitative electroencephalographic (qEEG) examinations in interferon (IFN)-α-treated chronic hepatitis C patients. However, it remains unclear how this alteration could be assessed. We evaluated the correlation between the qEEG changes and three tests of mental status, including the Mini-Mental State Examination (MMSE), in such patients. This is the first study to undertake a clinical evaluation of the adverse effects on brain function d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
24
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(25 citation statements)
references
References 11 publications
1
24
0
Order By: Relevance
“…EEG recordings and qEEG analyses employed in the present study have been described in previous studies [6,7,8,9]. Briefly, EEG recordings (directly after checking for α-blocking) were obtained from each patient during a resting awake condition with their eyes closed.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…EEG recordings and qEEG analyses employed in the present study have been described in previous studies [6,7,8,9]. Briefly, EEG recordings (directly after checking for α-blocking) were obtained from each patient during a resting awake condition with their eyes closed.…”
Section: Methodsmentioning
confidence: 99%
“…Previously, we reported diffuse EEG slowing in patients with IFN-α-treated chronic hepatitis C using quantitative EEG (qEEG) techniques [6]. Additionally, we reported that the qEEG change in IFN-α-treated chronic hepatitis C was related to Mini-Mental State Examination score [7], patient age [8], and the severity of chronic hepatitis C based on liver biopsy [9]. However, no study has assessed the relationship between IFN-induced depression and EEG changes using a quantitative approach.…”
Section: Introductionmentioning
confidence: 99%
“…Although these previous studies assessed the relationship between IFNα treatment in chronic hepatitis C and EEG changes in patients using quantitative EEG (qEEG), the number of patients studied was small. In this review article, we describe (1) qEEG changes in IFNα-treated chronic hepatitis C patients [7], (2) the relationship between qEEG changes and patient age [8], (3) the severity of the disease [9] and (4) the Mini-Mental State Examination (MMSE) [10] score [11], and (5) IFNα-induced depression [12]. These results provide the first evaluation of qEEG findings assessed in a large number of IFNα-treated chronic hepatitis C patients.…”
Section: Introductionmentioning
confidence: 99%
“…Other studies have reported that electrophysiological changes, as shown on quantitative electroencephalograms, were associated with cognitive impairment during IFN treatment (7,8,14). Thus electrophysiological assessments may be sensitive to changes in cognitive impairment.…”
mentioning
confidence: 96%
“…ment (9,10,12). In addition, it has been suggested that physiological alterations occurring among patients receiving IFN-α treatment are associated with cognitive impairment (8). However, in the Hepatitis C Antiviral Long-term Treatment Against Cirrhosis Trial (HALT-C) study, Fontana et al showed that the frequency of cognitive impairment for patients with CHC did not increase at week 24 compared with baseline, suggesting that the cognitive function of patients with CHC did not worsen with peg IFN and ribavirin retreatment (3).…”
mentioning
confidence: 99%